Dynamics characteristic of connecting rod for four stroke engine - Adi Firdaus, Hat (2009)
This thesis deals with computational modal analysis of the connecting rod. The objective of this project is to investigate the effect of the modal updating to the dynamic characteristic of the connecting rod, and to develop a finite element model of structure. This project also studies the vibration of a connecting rod in order to determine its natural frequencies and mode shapes. The connecting rod of the Modenas Kriss 110 cc engine has been considered as the model of the analysis. Structural modeling of connecting rod has been developed using SOLIDWORK software. The structural model then imported to the MSC.PATRAN software for generating mesh and the numerical analysis was performed using MSC.NASTRAN software. Mesh sensitivity have been done in order to determine the suitable mesh for further analysis. Result of the modal analysis show that first mode of the connecting rod occur at 77.411 Hz with higher displacement equal to 16.7mm. Natural frequency of the connecting rod can be increase by improvement of the properties of the material. In modal updating analysis show that material with lower density and higher Modulus of Young’s will increase the natural frequency of the connecting rod.